Failure Analysis (Experimental and Numerical Approach) of Gas Turbine Generator Cooling Fan in Comparison between using 2types (14° and 19° Angle of Attack) of Blades - JAHANGIRI, Ali; TORSHIZI, Seyed Ebrahim Moussavi; NIKRAVESH, Seyed Majid Yadavar (Engineering Transactions, 2014)
In gas turbine power plants, a fan is used as a cooling system to dissipate generated heat in coils (copper conductors) and generator electric circuits at the end sides of its rotor. In some cases, fracture of blades causes a short circuit between rotor and stator and consequently generator explosion and financial problems. The fracture of cooling fan blades has occurred five times at the turbine side of the generator in our case of study, just 100hr after resuming operations after an overhaul. Using numerical analysis as well as laboratory investigation – including visual inspections, metallography and SEM – can help better find failure problems that cause blade failures. A series of numerical analysis was performed to diagnose the possible cause of failure. CFD analysis is used to study the airflow distribution in order to observe probable separation phe- nomenon and pressure forces as they are imposed on fan blades due to operation. A finite element method was utilized to determine the stresses and dynamic characteristics of the fan blade (natural frequencies, stresses and vibrations). Key words: fatigue failure, dimple rupture, fan blade, scanning electron microscope (SEM), resonance, fan blade angle of attack, computational fluid dynamic (CFD), finite elements.